The Association Between Three Adipocytokines (Adiponectin, Resistin and Visfatin) And Thyroid Status in Patients With Type 2 Diabetes Mellitus and Autoimmune Thyroiditis - Sotak, Štefan; Schroner, Zbynek; Lazúrová, Ivica; Felsöci, Marek; Jochmanová, Ivana; Petrášová, Darina; Bertková, Izabela; Mitníková, Miriam; Nováková, Božena; Wagnerová, Hedviga; Bobelová, Oľga (Physiological research, 2021)
Autoimmune thyroiditis (AIT) and type 2 diabetes mellitus (DM2) are the most common endocrinological diseases worldwide. Relation between these diseases explains several hypotheses. One of them is influence of some adipocytokines. This study evaluated association between three adipocytokines (adiponectin, resistin and visfatin) and thyroid and glycid status in patients with DM2 and AIT compared to the control group (CG). The group consisted of four subgroups: patients with DM2 without thyreopathies, patients with AIT on substitution therapy without diabetes and prediabetes, patients with DM2 and AIT on substitution therapy and healthy subjects as the CG. We investigated parameters of thyroid and glucose metabolism and serum levels of three adipocytokines. The mean level of resistin in the group of patients with diabetes and thyroiditis was significantly higher than in patients with thyroiditis without diabetes and than in the CG. We found a weak negative correlation between visfatin and fasting glucose levels in patients with thyroiditis without diabetes. We detected a weak negative correlation between resistin and glycated haemoglobin and a weak negative correlation between visfatin and thyroid gland volume in patients with diabetes without thyroiditis. In the CG we determined a weak positive correlation between visfatin and free thyroxin. Our results are consistent with several studies, which confirmed association between AIT and adipocytokines.
Keywords: Thyroid Gland; Young Adult; štítná žláza; Ultrasonography; Male; glykovaný hemoglobin; mladý dospělý; cytokiny; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Diabetes Mellitus, Type 2; Thyroiditis, Autoimmune; diabetes mellitus 2. typu; lidé; ženské pohlaví; studie případů a kontrol; Glycated Hemoglobin; Humans; Nicotinamide Phosphoribosyltransferase; Adipokines; Cytokines; Female; nikotinamidfosforibosyltransferasa; adipokiny; lidé středního věku; autoimunitní tyreoiditida; ultrasonografie; Middle Aged